Asymptomatic malaria in the clinical and public health context. Issue 12 (2nd December 2019) - Cheaveau, James; Mogollon, Daniel Castaneda; Mohon, Md Abu Naser; Golassa, Lemu; Yewhalaw, Delenasaw; Pillai, Dylan R
ABSTRACT: Introduction : Historically, the global community has focused on the control of symptomatic malaria. However, interest in asymptomatic malaria has been growing, particularly in the context of malaria elimination. Areas covered : We undertook a comprehensive PubMed literature review on asymptomatic malaria as it relates to detection and elimination with emphasis between 2014 and 2019. Diagnostic tools with a low limit of detection (LOD) have allowed us to develop a more detailed understanding of asymptomatic malaria and its impact. These highly sensitive diagnostics have demonstrated that the prevalence of asymptomatic malaria is greater than previously thought. In addition, it is now possible to detect the malaria reservoir in the community, something that was previously not feasible. Asymptomatic malaria has previously not been treated, but research has begun to examine whether treating individuals with asymptomatic malaria may lead to health benefits. Finally, we have begun to understand the importance of asymptomatic malaria in ongoing transmission. Expert opinion : Therefore, with malaria elimination back on the agenda, asymptomatic malaria can no longer be ignored, especially in light of new ultra-sensitive diagnostic tools.